E-logistics for the chemical industry - Teo, Derek Joseph Cheng Choon. (2008)
In this dissertation, the case of SS Chemicals has been used to illustrate the various processes involved in a typical chemical industry and the disadvantages of such. The focus is the conceptual move to e-logistics, basing on SS Chemicals scenario and how the various functions can be integrated and the benefits that can be derived. The requirements for implementing e-logistics, the various approaches that can be used to implement have also been analysed, together with reasons why e-logistics can fail.